Prevalence of Cardiovascular Risk Factors in the Middle-Aged and Elderly Population of a Nigerian Rural Community - E. C. Ejim; C. I. Okafor; A. Emehel; A. U. Mbah; U. Onyia; T. Egwuonwu; J. Akabueze; B. J. Onwubere (Journal of Tropical Medicine)
Cardiovascular diseases (CVDs) causes of worldwide preventable morbidity and mortality. CVDs are a leading cause of mortality and morbidity in developing countries, and rates are expected to rise over the next few decades. The prevalence of CVD risk factors is dramatically increasing in low-and middle-income African countries, particularly in urban areas. We carried out a cross-sectional population-based survey in Imezi-Owa, a rural community in South East Nigeria to estimate the prevalence of major cardiovascular risk factors in both men and women aged 40–70 years. A total of 858 individuals made up of 247 (28.8%) males and 611 (71.2%) females were recruited. The mean age of the subjects was 59.8±9.9 years. The prevalence of the different cardiovascular risk factors among the 858 subjects was as follows: hypertension 398 (46.4%) subjects, generalized obesity as determined by BMI 257 (30%) subjects, abdominal obesity 266 (31%) subjects, dysglycaemia 38 (4.4%) subjects and hypercholesterolaemia 32 (3.7%) subjects. Prevalence of hypertension and dysglycaemia was higher in men while the others were higher in women. Only hypertension (P=.117) and hypercholesterolaemia (P=.183) did not reveal any significant association with gender. Prevalence of CVD risk factors was highest in subjects aged 65 to 70 years.